TINDAKAN KEBIRI BAGI PELAKU KEKERASAN SEKSUAL TERHADAP ANAK (Kajian Perspektif Hukum Islam dan Hukum Positif di Indonesia) - Desy Maryani (AL IMARAH : JURNAL PEMERINTAHAN DAN POLITIK ISLAM, 2017)
The government needs to re-examine the provision of additional punishment that is considered a violation of human rights violated human rights and not in accordance with Islamic Shari'a. The results of the study show that (1) the punishment of the noble violates the Shari'a of Islam so it is forbidden with three reasons: a) Islamic shari'ah has unlawfully prohibited the human being, without any dissenting opinion (khilafiyah) among fuqaha, b) Islamic shariah has set penalties for pedophile who commit acts of immorality and rape according to the details of the facts of his deeds, so that it may not (haram) carry out any kind of punishment outside the provisions of Islamic Sharia, c) in the case of the method of using a chemical injection method, namely injected estrogen hormone, from the other side, because it resulted in castrated men having physical characteristics such as women. Yet Islam has forbidden men to resemble women or vice versa women resemble men. (2) In the regulation of legal policy for perpetrators of sexual violence against children is contained in the Criminal Code and the issuance of Law no. Law No. 23 of 2002, Law no. 35 of 2014 until the issuance of Law no. 1 Year 2016 on Child Protection